Viability of Lactobacillus plantarum NCIMB 8826 immobilized in a cereal-legume complementary food "weanimix" with simulated gastrointestinal conditions. (April 2021) - Kyereh, Emmanuel; Sathivel, Subramaniam
Abstract: Three cereal-legume complementary foods ( weanimix ) were formulated and evaluated for their ability to enhance the survival of probiotic bacteria Lactobacillus plantarum NCIMB 8826 in simulated gastrointestinal tract conditions. The three different blends of weanimix: MCPPM (maize:cowpea:peanut:powdered milk), MCP (maize:cowpea:peanut) and MC (maize:cowpea) were used. L. plantarum was inoculated and cultured in the weanimix slurry media to immobilize the cells. L. plantarum free cells in MRS broth were used as a control. Simulated gastric fluid (SGF) of pH 2.5, 3.0 and 3.5, and bile salt (0.3 and 1 g/100 ml of ox gall) were used to simulate the gastrointestinal conditions. The three complementary blends offered a protective shield, which improved cell viability in SGF at all pH levels. L. plantarum survived well in MCPPM, MCP and MC with <2 log cell reduction compared with the free cells reduction of 5 log after 180 min of incubation for each pH. For bile tolerance, viable cell counts in the weanimix were higher than the free cells after 24 h suspension. The results of the study showed that weanimix improved the survival and viability of L. plantarum .